Precision Immunotherapy of Cancer - Hoyle, Brian (MD Conference Express, 2014)
The traditional cancer therapy triumvirate of chemotherapy, radiation, and surgery is today being augmented with vaccines, cytokines, antibodies, targeted small-molecule drugs, and cell-based therapies such as immunotherapy. The hope is that combination therapies involving immune-based approaches will greatly enhance long-term survival. This article provides an overview of genetically modified cancer therapy with T cells.